Use of the recycled aggregates – a way to the sustainable rebuild - KOVALCHUK, Oleksandr; ZOZULYNETS, Viktoriia; IVANYCHKO, Vasyl; KOPOTUN , Ruslan (Ways to Improve Construction Efficiency, 2024)
The question of wide use of recycled aggregate on the basis of demolition wastes rises sharp due to the different points of view: from the point of view of necessarity to utilize multitoned wastes appeared because of war influence, from the point of view of strong will to rebuild the country and also because of the need to have economical, ecological and natural sources rational consumption. In the same time, such recycled products could also have high defective structure because of their origin and demanding to implement the special technology of their treatment and use. Peculiarities of Ukrainian national experience for such systems if their composition. Namely possible presence of organic compounds and products of war activities, that leads to some difficulties in structure formation in concretes on their basis. As a potential method to decrease defective structure appearance in concrete is introduction of modifying admixtures, promoting self-healing of the structure elements in concrete, and also use of alternative cements, able to resist against high structure movement, appeared due to the presence of organic additives. Also, use of alternative cements makes it possible to widen raw materials base for rebuilding of Ukraine, so far as present source even taking into account perspective production of 20 million tons of the cement with the need more than 30 million tons per year is not enough. The implementation of the results of this study will not only solve the issue of recycling large-scale industrial waste, but also significantly increase the pace of construction and restoration of infrastructure, damaged and destroyed housing stock by obtaining a large raw material resource in the form of secondary recycled aggregate as a local raw material. It will also be possible to expand the use of alkaline binders in construction production and increase the use of technogenic waste, represented by concrete buildings and structures that require immediate and complete recycling. Based on the results of the work, recipes for concrete mixtures using recycled aggregates and methodological foundations for regulating the self-healing processes of the structure of such material will be developed.